Analisis Proses Komunikasi Interpersonal Guru dan Siswa Tunarungu dalam Penggunaan Komunikasi Verbal dan Nonverbal di SLB Negeri 1 Padang - Vadisa; Indria Flowerina (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This research is based on the communication skills of deaf students which can be developed if there is one of the supporting factors. You can know that deaf children are those who experience a lack or loss of the ability to hear either partially or completely due to the malfunctioning of part or all of the deterrent device in life everyday that has a complex impact on life . The limited communication skills that deaf children have, especially in verbal communication skills , are a reason for them to use non-verbal language (signs) for interact with each other . The purpose of this study was to determine the interpersonal communication process of deaf teachers and students in the use of verbal and nonverbal communication at SLB Negeri 1 Padang. The research method used in this study is a descriptive qualitative research method with data collection techniques that include interviews, observations and documentation. The results showed that the interpersonal communication process of deaf teachers and students was good, but in the use of verbal and nonverbal communication there were obstacles, namely in the difficulty of understanding deaf students and the use of language due to limited vocabulary possessed. In this case, SLB Negeri 1 Padang has not implemented an official language such as SIBI (Indonesian Sign Language System) in the communication process between teachers and deaf students because deaf students are more accustomed to everyday sign language (mother tongue).